Pengaruh Latihan Variasi Terhadap Kemampuan Passing Bawah Bolavoli Siswi puteri Ekstrakurikuler SMA Negeri 1 Rokan IV Koto Kabupaten Rokan Hulu - Jihatun Fitrah; Slamet '; Kristi agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on my observations that have been made against the female students who take part in extracurricular volleyball at SMAN 1 RokanIV Koto Rokan Hulu District seem that passing volleyball of female students were still not good yet, it was due to the absence of the provision of special training under the female students’ passing. Female students’ did not understand the technique of passing down the right well, due to lack of exercise technique because it has not been given by the teacher as a builder. When receiving the ball arm is too high, the body is too low because the waist is bent so that the pass was too low and fast is supposed bent knee. Separate arm shortly after receiving the ball. The ball landed at the local arm of the elbow. The purpose of this study was to look at the exercise variations effect to passing ability of female students’ passing on volleyball extracurricular at sman 1 rokan iv koto rokan hulu district. As the population used in this study is female students’ who joined extracurricular volleyball at SMAN 1 Rokan IV Koto Rokan Hulu District that consist of 18 people. The sampling technique is total sampling, where all the population sampled (Sugiyono, 2010: 96) in this study were 18 female students who partsicipated in extracurricular female volleyball at SMAN 1 Rokan IV Koto Rokan Hulu District. The instrument used to collect data that pre-test and post test in this study used a test passing below. Data were analyzed using t test. Based on the analysis of pre-test and post-test, it appears that there is an average increase of 3.58% with a t test that t = 11.068> t table = 1.740.Keywords: Exercise Variation, Passing Down Capabilities